Evidence of coupled autotrophy and heterotrophy on plastic biofilms and its influence on surrounding seawater. (15th December 2022) - Conan, Pascal; Philip, Léna; Ortega-Retuerta, Eva; Odobel, Charlène; Duran, Clélia; Pandin, Caroline; Giraud, Carolane; Meistertzheim, Anne-Leila; Barbe, Valérie; Ter Hall, Alexandra; Pujo-Pay, Mireille; Ghiglione, Jean-François
Abstract: We measured phytoplankton primary production and heterotrophic bacterial activities on microplastics and seawater in the Northwestern Mediterranean Sea during two 3-month spring periods over 2 consecutive years. Microorganisms growing on a 5 mm diameter low density polyethylene films (LDPE; 200 μm thick) faced two contrasting conditions depending on the year. Spring 2018 was characterized by consistent nutrient inputs and bloom development. In spring 2019, nutrient inputs and bloom were low. For the first time, we observed a clear coupling between primary production and heterotrophic prokaryote production on microplastics during both years, but with different intensity between years that reflected the crucial role of the trophic environmental conditions (nutrient supply) in shaping microbial activities on plastics. We found that high primary production on plastics could support the whole (net autotrophy) or the majority of the bacterial carbon demand needed for heterotrophic activities, supplemented by other carbon sources if surrounding waters are highly productive. We propose that microbial activity on plastics influences the microbial community in the surrounding seawater, especially when the environmental conditions are less favorable. An illustrative image of the role of plastics in the environment could be that of an inverter in an electrical circuit that mitigates both positive and negative variations. Our results highlight the potential role of the plastisphere in shaping biogeochemical cycles in the context of increasing amounts of plastic particles in the marine environment. Graphical abstract: Image 1 Highlights: Microplastics are the seat of strong coupled autotrophic and heterotrophic activities. Microplastics can be either a sink or a source of organic matter for the environment. Microplastic biofilms are relatively unaffected by environmental nutrient depletion. Marine primary production is enhanced by material released from the plastic biofilms.